OPTIMASI PENUGASAN MELALUI PENERAPAN HUNGARIAN METHOD DAN NEW ALTERNATE METHOD - HAMMA, NOVITA TRIANI; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 13 No 1 (2024), 2024)
One of the materials discussed in operations research is linear programming, which also discusses models of transportation. The assignment problem can be viewed as a special case of the transportation model. One method that is often used to solve assignment problems is the Hungarian method. Over time, there have also been more and more alternative methods to streamline processing time in solving assignment problems, one of which is the new alternate method.   The purpose of this  research is to form an optimal scheduling with minimum processing time.  The data used in this study is secondary data obtained from CV Bagus Classic. The data consists of the number of workers, type of work, and the time needed to complete the work by each worker. As a result of this research, it was found that the minimum assignment time was achieved when using the Hungarian method compared to using the new alternate method or before using both methods .